Water Resistance of Fiberglass Reinforced Plywood during Prolonged Water Exposure. - Jakimovska popovska, Violeta; Iliev, Borche (Faculty of Forestry and Wood Technolgy, University in Zagreb, 2023)
Тhe aim of this research is to study the water absorption and thickness swelling of plywood reinforced with fiberglass fabrics pre-impregnated with alcohol-soluble phenol-formaldehyde resin during prolonged water exposure. Four experimental reinforced plywood models were made from peeled beech veneers with thickness of 1.5 mm and 1.85 mm bonded with the same resin used for fabric pre-impregnation. In each model, sheets of pre-impregnated fabric (prepreg) were incorporated in different adhesive layers of the plywood structure. One additional model was made without reinforcements as comparing plywood model. On the basis of the obtained data for the changes of water absorption and thickness swelling of reinforced plywood after immersion in water continuously for a period of 192 days, water resistance of experimental plywood was evaluated. The research results showed that the application of fiberglass prepreg as reinforcement in plywood structure significantly decreases the values of water absorption and thickness swelling. After full water treatment plywood models have good dimensional stability and do not show deformations.
Keywords: Fiberglass, plywood, prepreg, reinforcement, water exposure, water resistance